Влияние некоторых антропических факторов на формирование гемиптерокомплексов в Украинских Карпатах - Рошко, Г.М. (Вестник зоологии, 1973)
Under the effect of human economic activity the hemipterocomplexes of many biotopes are changed. Some species of Hemiptera find no suitable conditions for existence under changed environment. At the present time most biotopes in the region of the Ukrainian Carpathians were subjected to human activity to some extent. The changes in the hemipterocomplexes are observed in cutting areas, in places of marshland reclamation in pasture lands, in meadows with regular haying, in places of shrubbery stubbing, in settlements. These changes are especially noticeable for the recent twenty years in the region of the Carpathians, first of all, in lowlands and foothills.